Effects of high CO2 and hypoxia on the embryonic development of European cuttlefish (Sepia officinalis) - Amaduzzi, Angelica (2022)
The increasing atmospheric CO2 concentrations due to anthropic influence is causing the acidification of the oceans, which often co-occurs with hypoxia events. These are becoming a growing concern for marine ecosystem and for aquaculture due to the potential consequences on early life stages of marine animals and in particular for invertebrates, who form their internal skeletons out of calcium carbonate. The European cuttlefish (Sepia officinalis) is an excellent model to assess the effects of climate change, since it possesses a calcium carbonate structure from early development that grows very fast with a short life cycle. The present thesis aims to determine the effects of two environmental stressors, high CO2 environment and hypoxia events, in European cuttlefish embryogenesis, hatching rates and physiological characterisation through metabolic rates. Two separate experiments were performed. During the first, the cuttlefish eggs were kept in an indoor semi-open system with temperature maintained stable at 20°C and exposed to an acute event of hypoxia during the embryonic development (either day 10 or day 20). In the second experiment, cuttlefish eggs were kept in an outdoor open seawater system and exposed to high CO2 or to high CO2 plus an acute hypoxia event (either day 10 or day 20). The data obtained from the first experiment suggested that the embryos, kept at a temperature of 20°C can manage an acute hypoxia event without substantial consequences on their development. In the second outdoor experiment a much lower hatching rate was recorded, compared to the first experiment. This might be reconnected to the higher water temperature. Based on these data, it can be hypothesised that temperature could be one of the main key factors for cuttlefish eggs survival. Even so, it is not clear which is the threshold temperature for cuttlefish during the embryonic development.